From Latin America to Oceania: The Historic Dispersal of Sweetpotato Re-examined Using AFLP - Rossel, G.; Kriegner, A.; Zhang, D.P. (2001)
Although originally domesticated in tropical America, the sweetpotato (Ipomoea batatas (L.) Lam.) has a long cultivation history in Oceania. While the post-Columbus dispersal of sweetpotato to Asia and Oceania is well documented, the hypothesis that there was prehistoric transfer by Peruvian or Polynesian voyagers from Peru to Oceania has long been a controversial issue. The objective of this study was to assess the genetic diversity and interrelationship of sweetpotato cultivars from Oceania and Latin America and to test the hypothesis of human transfer of this crop to the Pacific Islands in prehistoric time. Seventy-six sweetpotato cultivars from Peru-Ecuador, Mexico, the Philippines and eight Oceania countries were analyzed using amplified fragment length polymorphism (AFLP). Multidimensional scaling (MDS) and analysis of molecular variance (AMOVA) revealed wide genetic variation in the Oceania gene pool, greater than that of Peru-Ecuador. There was a significant sweetpotato “gene flow” from Mexico to Oceania. In contrast, there is little association between the Peru-Ecuador germplasm and that of Oceania. These results suggest that Peru-Ecuador may not be the source of the Oceania germplasm. Natural dispersal from Mesoamerica is an alternative explanation to the ‘Kumara hypothesis’ for the origin of the Oceania sweetpotato